Late Oligocene–Miocene mantle upwelling and interaction inferred from mantle signatures in gabbroic to granitic rocks from the Urumieh–Dokhtar arc, south Ardestan, Iran. Issue 12 (10th September 2017) - Babazadeh, Shahrouz; Ghorbani, Mohammad Reza; Bröcker, Michael; D'Antonio, Massimo; Cottle, John; Gebbing, Thorsten; Carmine Mazzeo, Fabio; Ahmadi, Parham
ABSTRACT: The south Ardestan plutonic rocks constitute major outcrops in the central part of Iran's Cenozoic magmatic belt and encompass a wide compositional spectrum from gabbro to granodiorite. U–Pb laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) dating of zircon three granodiorites yielded ages of 24.6 ± 0.1, 24.6 ± 0.1, and 24.5 ± 0.1 Ma. For tonalitic rocks, internal Rb–Sr isochron ages (biotite, feldspars) indicate cooling ages of 20.4 ± 0.1, 20.5 ± 0.1, and 22.3 ± 0.1 Ma, which are slightly younger than the zircons' ages. The limited variations in their Sr–Nd isotope ratios indicate derivation from an asthenospheric mantle source. A geodynamic model is presented in which late Oligocene–Miocene rollback of the Neotethyan subducting slab triggered asthenospheric upwelling and partial melting in the south Ardestan. These melts were subsequently modified through fractional crystallization and minor crustal contamination en-route to the surface. Plagioclase + orthopyroxene-dominated fractional crystallization accounts for differentiation of gabbro to gabbroic diorite, whereas fractionation of clinopyroxene, titanomagnetite, and orthopyroxene led to differentiation of gabbroic diorite to diorite. Amphibole fractionation at deeper levels led to the development of tonalites.